1999
DOI: 10.1046/j.1526-4610.1999.3910716.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine for Migraine Prophylaxis: A Double‐Blind Trial

Abstract: Even if preliminary and to be confirmed, these data seem to support the use of fluoxetine in the treatment of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 0 publications
1
35
0
5
Order By: Relevance
“…29 After the 6 months, pain index scores for the fluoxetine group decreased from 135 (baseline) to 41.3 (SD Ϯ 63.8; p ϭ 0.001). The placebo group pain index was 98 at baseline and 61.1 at 6 months (SD Ϯ 57.7; p ϭ 0.07); however, differences were noted between treatment groups for baseline measures.…”
mentioning
confidence: 91%
“…29 After the 6 months, pain index scores for the fluoxetine group decreased from 135 (baseline) to 41.3 (SD Ϯ 63.8; p ϭ 0.001). The placebo group pain index was 98 at baseline and 61.1 at 6 months (SD Ϯ 57.7; p ϭ 0.07); however, differences were noted between treatment groups for baseline measures.…”
mentioning
confidence: 91%
“…[3][4][5][6] There is increasing evidence that use of angiotensin converting enzyme (ACE) inhibitors can substantially reduce the frequency and severity of migraine attacks. Quite recently, a controlled clinical trial demonstrated a clear improvement of migraine, in terms of headache duration and severity, during ACE inhibition therapy with lisinopril when compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Triptans, selective serotonin 5-HT1B/1D agonists, are very effective acute migraine drugs [93,94]. Although conflicting results have been reported about the use of SSRIs (selective serotonin reuptake inhibitors) in migraine prevention [95][96][97][98], trycyclic antidepressants such as amitriptyline are currently employed in migraine prophylaxis with evidence supporting their effectiveness for use [99,100]. Thus genes in the serotonergic system have been investigated as potential candidates to mediate susceptibility to migraine.…”
Section: Neurotransmitter Functionmentioning
confidence: 99%